PENGARUH PENGGUNAAN READING ALOUD UNTUK MENINGKATKAN KEMAMPUAN MELAFALKAN BAHASA INGGRIS - Muchamad Arif; Fitri Rofiyarti (MOTORIC, 2022)
This research aimed to determine the success of using the reading aloud strategy to improve English pronunciation skills. The reading material has a different topic in each meeting. This research observation was conducted for 3 meetings. It used the qualitative descriptive method. The research subjects were 13 students, consisting of 11 female students and 2 male students. The results of the study showed that the application of reading aloud could improve the ability to pronounce English. Then, this implementation also helped students build a collection of words or vocabulary. Furthermore, this strategy helped students improve comprehension of a text. In addition, this implementation could help classroom management. Teachers could limit student activities as well as control their activities. Keywords: reading aloud, pronunciation, English, online english dictionary